Retrodeformation and muscular reconstruction of ornithomimosaurian dinosaur crania - Andrew R. Cuff; Emily J. Rayfield (PeerJ, 2015)
Ornithomimosaur dinosaurs evolved lightweight, edentulous skulls that possessed keratinous rhamphothecae. Understanding the anatomy of these taxa allows for a greater understanding of “ostrich-mimic” dinosaurs and character change during theropod dinosaur evolution. However, taphonomic processes during fossilisation often distort fossil remains. Retrodeformation offers a means by which to recover a hypothesis of the original anatomy of the specimen, and 3D scanning technologies present a way to constrain and document the retrodeformation process. Using computed tomography (CT) scan data, specimen specific retrodeformations were performed on three-dimensionally preserved but taphonomically distorted skulls of the deinocheirid Garudimimus brevipes Barsbold, 1981 and the ornithomimids Struthiomimus altus Lambe, 1902 and Ornithomimus edmontonicus Sternberg, 1933. This allowed for a reconstruction of the adductor musculature, which was then mapped onto the crania, from which muscle mechanical advantage and bite forces were calculated pre- and post-retrodeformation. The extent of the rhamphotheca was varied in each taxon to represent morphologies found within modern Aves. Well constrained retrodeformation allows for increased confidence in anatomical and functional analysis of fossil specimens and offers an opportunity to more fully understand the soft tissue anatomy of extinct taxa.